My brother Sam is dead - Collier, James Lincoln 1928-; Collier, Christopher 1930- (New York Scholastic Inc., 1974)
Recounts the tragedy that strikes the Meeker family during the Revolution when one son joins the rebel forces while the rest of the family tries to stay neutral in a Tory town.
Keywords: United States -- History -- Revolution, 1775-1783 -- Juvenile fiction; United States -- History -- Revolution, 1775-1783 -- Fiction